2022
DOI: 10.1177/09504222221087614
|View full text |Cite
|
Sign up to set email alerts
|

Business students’ perceptions of Dutch higher educational institutions in preparing them for artificial intelligence work environments

Abstract: The application of artificial intelligence (AI) brings new demand to the job market. The concern now is whether higher education institutions (HEIs) have adequately prepared young learners to work in an AI work environment. This research seeks to explore business students’ perceptions of their HEIs in the Netherlands in preparing them for AI work environments. A questionnaire-based survey was completed by 95 students from 27 HEIs in the Netherlands. The findings show that these students believe that their HEIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…A study of the use of chatbots in business education also reported favourable user feedback with students citing positive learning experience due to chatbots' responsiveness, interactivity, and confidential learning support (Chen et al, 2023). Most students agreed that AI have a profound impact on their disciplines and future careers (e.g., Bisdas et al, 2021;Gong et al, 2019;Sit et al, 2020) and expressed an intention to utilise AI in their learning and future practice (e.g., Bisdas et al, 2021;Lee et al, 2022), and thus viewed integration of AI as an essential part of university curricula (e.g., Abdelwahab et al, 2022;Bisdas et al, 2021;Gong et al, 2019;Yüzbaşioğlu, 2021).…”
Section: Student Perceptions Of the Use Of Genai In Higher Educationmentioning
confidence: 99%
“…A study of the use of chatbots in business education also reported favourable user feedback with students citing positive learning experience due to chatbots' responsiveness, interactivity, and confidential learning support (Chen et al, 2023). Most students agreed that AI have a profound impact on their disciplines and future careers (e.g., Bisdas et al, 2021;Gong et al, 2019;Sit et al, 2020) and expressed an intention to utilise AI in their learning and future practice (e.g., Bisdas et al, 2021;Lee et al, 2022), and thus viewed integration of AI as an essential part of university curricula (e.g., Abdelwahab et al, 2022;Bisdas et al, 2021;Gong et al, 2019;Yüzbaşioğlu, 2021).…”
Section: Student Perceptions Of the Use Of Genai In Higher Educationmentioning
confidence: 99%
“…Several publications were identified that looked into student perceptions of GenAI, which included Abdelwahab et al (2023), Banihashem et al (2023), andMartín-Ramallal et al (2022). Even though these studies are grounded in different contexts, i.e.…”
Section: Effects Of Genai On He Student Learningmentioning
confidence: 99%
“…The era of AI presents both challenges and opportunities for education [33,34]. With the emergence of new learning channels, such as learning management systems based on digital textbooks, personalized learning through big data analysis, interactive technologies utilizing voice recognition and speech synthesis, and chatbots driven by natural language processing, the majority of AI technologies have educational and instructional applications [35,36].…”
Section: Students' Perception Of the Usefulness Of Ai In Their Studymentioning
confidence: 99%
“…Abdelwahab et al [34] in their study on 95 students from 27 higher education institutions (HEI) in the Netherlands found that students and graduates studying at HEIs in the country generally believe that their knowledge and understanding of AI are inadequate to grasp its potential impacts on their future careers. Therefore, the following hypothesis is proposed: H3.…”
Section: Students' Perception Of Work Skills For the Futurementioning
confidence: 99%